Smart Device to Smart Device Communication - Mumtaz, Shahid; Rodriguez, Jonathan (Springer International Publishing : Imprint: Springer, 2014)
This book presents a comprehensive analysis on D2D communication over LTE-A band, while explaining D2D communication. The book considers 3GPP LTE-A as a baseline and explains all fundamental requirements for deploying D2D network under cellular systems from an architectural, technical and business point of view. The contributors explain the standardization activities of Release 12 of LTE-A, which has been recently acknowledged as support of D2D communication in LTE-A. The text updates the research community on the D2D roadmap as well as new features emerging for consideration in 3GPP.